Direct and residual impact of boron fertilization improves the crop yield, nutrient contents, nutrient uptake, and nutrient use efficiencies in cauliflower–cowpea–okra sequence in an acidic Inceptisol of North East India. (10th February 2022) - Bhupenchandra, Ingudam; Basumatary, Anjali; Dutta, Samiron; Nabachandra Singh, L.; Das, Anup; Singh, Laishram Kanta; Devi, Soibam Helena; Sinyorita, Soibam; Premabati Devi, Chingakham
Abstract: Field investigations were executed during the year 2015–17 to study the direct and residual effect of boron (B) application on crop yield, nutrient concentrations, nutrient uptake and nutrient use efficiencies in cauliflower–cowpea–okra cropping sequence in an acidic Inceptisol of Assam, India. To assess the direct effect of B fertilization in soil, five differential graded levels/doses of B (0, 0.5, 1.0, 1.5, and 2.0 kg ha −1 ) were applied using cauliflower as a test crop only. While cowpea and okra were grown as test crop to assess the residual effects of B fertilization, wherein B fertilization was exempted in both the crops. Recommended dose of fertilizers and farmyard manure was uniformly added in soil to the all the crops in the sequence. Results showed that among the differential B levels, the application of 2 kg B ha −1 in the cropping sequence exhibited a substantial yield augmentation up to 23.78, 7.15, and 20.61 t ha −1 in cauliflower, cowpea, and okra, respectively. Nutrient contents in leaves and edible portion of the crops, and nutrient uptake were recorded highest under 2 kg B ha −1 treatments as compared with the rest of other treatments. Also the highest nutrient use efficiencies in all the crops were registered under 2 kg B ha −1 . The overall results indicated that crop yield, nutrient content, nutrient uptake, and nutrient use efficiencies can be efficiently improved with the application of 2 kg B ha −1 in the cropping sequence.